Radiation and energy balance dynamics over a rapidly receding glacier in the central Himalaya. (16th July 2019) - Singh, Nilendu; Singhal, Mohit; Chhikara, Sudershan; Karakoti, Indira; Chauhan, Pankaj; Dobhal, Dwarika P.
Abstract : Driven by the strength in local land–atmosphere coupling, inter‐annual variability of larger‐scale atmospheric circulations primarily determines a glacier's response to warming in high Asia. In this study, micrometeorological measurements in conjunction with regional reanalysis data set were analysed to examine seasonal land–atmosphere coupling strength at a typical central Himalayan (CH) glacier where the influence of Indian summer monsoon (ISM) predominates relative to winter‐westerlies. Energy–water (E–W) exchange and coupling behaviour were studied for the Pindari glacier based on sub‐hourly measurements of radiative–convective flux, state parameters, and sub‐surface thermal profiles using cross‐correlations between various E–W balance components. Coupling was positive in summer and winter accumulation seasons. However, it remained strongest during ISM. Coupling reversed during seasonal transition phases concurrent with distinct seasonality in E–W components. Lead–lag relation between some variables showed strong association at diurnal‐scale (VPD– R n; VPD–LE; R n– G ), whereas some persisted beyond months ( R n–LE; Bowen ratio–precipitation; surface–air temperature). Weak association of variation of latent heat flux (LE) and rainfall was found during ISM at local scale than at regional scale, but with a lag, which was more prominent at regional scale. These observations indicate a seasonally variable coupling between E–W balance components through response–feedback mechanisms. Cross‐correlations of daily mean values of energy fluxes and meteorological variables reveal that R n and air temperature are the prime drivers of energy balance. Net radiative energy ( R n) dominates energy exchanges at the glacier–atmosphere interface (governed primarily by the variation in net shortwave radiation), contributed on average 62% of the melt energy. However, sub‐surface heat flux along with the turbulent fluxes was the energy sinks of 24 and 15%, respectively. This study would help understand and parameterize E–W exchange pathways for ISM dominated CH glaciers in coupled glacier–climate models. Abstract : Net radiation is the prime driver of energy balance. Land–atmosphere coupling (LAC) was positive in summer and winter accumulation seasons. Strongest and sustained LAC was observed during summer accumulation season. LAC during transition phases was negative and thus highly amenable to atmospheric perturbances. Lead–lag analyses indicate a seasonally variable response–feedback mechanism. In the figure, (a) location map of the Pindari valley (open box) and the Pindari glacier (red dot) in the Kumaun Himalaya, Uttarakhand, India. (b) Contour map of the Pindari and the adjoining Kaphni glacier. (c) Site photograph of the Pindari glacier (2017), yellow coloured dot designates the exact location of a micrometeorological station (inset) (30°15′44.69″N; 79°59′57.71″E). (d) Comparative site photographs showing the state of Pindari glacier in 1890 and 2017.